Estimation & Analysis Relationship between Growth rate GDP and Unemployment Rate In Iraqi Economic in Period (1990-2014) - عبيد باسم خميس (Journal of Economics and Administrative Sciences, 2017)
It reflects the gross domestic product in any country total output of goods and services by the size of the country’s citizens and foreign residents during the period of the year and reflect the contribution of the commodity sectors of the economy and the distribution and service in the composition of output. And gross domestic product in Iraq as an indicator dominated in the composition of oil output, along with the contribution of the service sector, as the gross domestic product is the output of a yield lien and subjected GDP in Iraq to a series of declines succession due to vibrations of the oil market during the economic blockade on the one hand and stop imported production inputs, lack of arriving in commodity sectors productivity on the other hand, which is reflected in the rise in unemployment in the Iraqi economy, therefore, use the index reflects increases in gross domestic product, and that the lack of use and the disruption of the labor force necessarily reflect the demise of the commodity cover production as a component of the output of a local, unemployment is Iraq’s most dangerous economic problems and traces its roots back to more than a quarter of a century, and varied forms different depending on the political and economic conditions seen in Iraq, as the real reasons for the phenomenon of lack of use dating back to transform the Iraqi economy from the development of the economy in the seventies into a war economy in the eighties and into financial speculative economy in the nineties and into the territory’s economy General extruder private and enhanced sector to the phenomenon of disguised unemployment and the use of incomplete in the third millennium, conclusion that high unemployment rates reflect the performance of the local market failure, and high unemployment rates have been rising gradually not decreasing, and indicates that the decline in GDP of non-oil despite the financial policies expansionist .